1972
DOI: 10.1080/00173137209428830
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscope Studies of Pollen of Cereals and other Grasses

Abstract: Andersen, S. Th. and Bxklsen, F. (Geological Survey of Dxmark.) Scaiiriirrg electroil riiicroscope srirdics of pollcri 01 ccreals arid other grasses. Gmna 12: 79-86, 1912.-Various authors disagree about the identification of ccrea! pollen based on phase 'contrast studies. Pollen of thc common cereals and some wild grasscs of a similar sire range \\ere examined with a scanning electron rnicroscopc. T h e pollen grains of ilordeuiri, Secalc, Triticiitii rrioiio-COCCIIIII, Agropyrorr, Aiiiriiopliila, Elyiiiiis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 4 publications
4
62
0
Order By: Relevance
“…For species within group one (figure 2), the pixels in the two clusters of lower intensity were turned into black pixels (background) and those in the two clusters of higher intensity were turned into white pixels (foreground; figure 3i). For species within groups two and three (figure 2), only pixels in the cluster of lowest intensity were turned into black pixels (background) and those in the other three were turned into white pixels (12). Group three (black plus signs) contains three species: Cynodon dactylon (6), Eragrostis mexicana (7) and Digitaria insularis (11).…”
Section: Classification Of Species Within Each Morphological Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…For species within group one (figure 2), the pixels in the two clusters of lower intensity were turned into black pixels (background) and those in the two clusters of higher intensity were turned into white pixels (foreground; figure 3i). For species within groups two and three (figure 2), only pixels in the cluster of lowest intensity were turned into black pixels (background) and those in the other three were turned into white pixels (12). Group three (black plus signs) contains three species: Cynodon dactylon (6), Eragrostis mexicana (7) and Digitaria insularis (11).…”
Section: Classification Of Species Within Each Morphological Groupmentioning
confidence: 99%
“…As a result, palynologists have attempted to increase the taxonomic precision of grass pollen by measuring characters such as pollen grain length, grain width, pore diameter and annulus width [8][9][10][11], and by noting differences in the organization of the grass pollen exine [5,9]. High-resolution scanning electron microscopy (SEM) studies have revealed a diversity of surface ornamentation patterns that may have taxonomic significance [5,[12][13][14][15][16] but are not visible when viewed using traditional light microscopy. However, exine ornamentation has not been widely used to classify grass pollen because of the difficulty in comparing the relatively small differences in surface patterning [5,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…This "diffraction limit" prevents conventional optical microscopes from imaging morphological features of sporomorphs that are less than 200-250 nm in size, and this is critical in the case of grass pollen. This is demonstrated by SEM images of grass pollen, which reveal that pollen morphology across Poaceae is characterized by a diverse suite of surface ornamentation patterns (Andersen and Bertelsen 1972;Page 1978;Peltre et al 1987;Chaturvedi et al 1998;Mander et al 2013;fig. 6).…”
Section: Seeing More: Microscopy In Palynologymentioning
confidence: 99%
“…This represents a barrier to the amount of morphological information that can be recovered from individual specimens, and we sense that this exerts a first-order control on the taxonomic resolution of sporomorph assemblages. There are many examples, including focused studies of a single group, such as grasses (Andersen and Bertelsen 1972;Page 1978;Peltre et al 1987;Chaturvedi et al 1998;Mander et al 2013; fig. 6), individual genera, such as Tilia (Moore et al 1991) and Quercus ( fig.…”
Section: Synthesis and Outlookmentioning
confidence: 99%
See 1 more Smart Citation